‘One does not take sides in these neutral latitudes’: Myles na gCopaleen and The Emergency - Asensio Peral, Germán (International Journal of English Studies, 2018)
The years of the Second World War (1939-1945), a period known as The Emergency in Ireland, were pivotal for the development of the nation. Immediately after the outburst of the war in the continent, the Fianna Fáil cabinet led by Éamon de Valera declared the state of emergency and adopted a neutrality policy. To ensure this, the government imposed strict censorship control, especially on journalism and the media. The aim of the censorship system was to ensure that war facts were presented as neutrally as possible to avoid any potential retaliation from any of the belligerents. This censorship apparatus, however, affected many intellectuals of the time who felt that their freedom of expression had been restrained even more. One of these dissenting writers was Brian O’Nolan (1911-1966), better known as Flann O’Brien or Myles na gCopaleen. For more than twenty-six years (1940-1966), he wrote a comic and satirical column in The Irish Times entitled Cruiskeen Lawn. In his column, O’Brien commented on varied problems affecting Dublin and Ireland as a whole. One of the many topics he began discussing was precisely Ireland’s neutral position in the war. Therefore, this paper aims at examining Ireland’s neutral position in the war as seen through a selection of columns from Cruiskeen Lawn, devoting special attention to the oppression of censorship and the distracting measures developed by de Valera’s government.